Temperature driven internal heat integration in an energy-efficient partial double annular column - Seo, Chaeyeong; Lee, Heecheon; Lee, Minyong; Lee, Jae W. (The Korean journal of chemical engineering, 2022)
This study presents a strategy for the internal heat integration of reactive distillation (RD) columns for concurrently producing 2-ethylhexyl dodecanoate and methyl dodecanoate. Because of a significant temperature difference in the two reactions, the two RD column process with each single reaction occurring in the respective column has lower energy consumption than the direct sequence consisting of one RD column followed by a non-RD column. Thus, internal heat integration in a partial double annular configuration is introduced on the basis of the two RD column process. In the new annular RD configuration, heat is transferred from the outer column shell having a high-temperature exothermic reaction to the inner shell with a low-temperature endothermic reaction. By using the concept of pinch temperature, we determine the heat transfer stages to secure sufficient temperature driving force. For the same product purity and reaction extent, the internal heat integrated distillation column (HIDiC) shows lower internal flow-rate and energy consumption than the other sequences of the direct sequence and the reactive dividing wall column (RDWC). The total utility consumption of the HIDiC with a partial double annular structure was reduced by 15.4% and 14.4% compared to the direct sequence and the RDWC, respectively.